1998
DOI: 10.1038/sj.bmt.1701070
|View full text |Cite
|
Sign up to set email alerts
|

Late onset Epstein–Barr virus-associated lymphoproliferative disease after allogeneic bone marrow transplant presenting as breast masses

Abstract: Summary:donor. GVHD prophylaxis consisted of T cell depletion of the donor marrow with T10-B9 (an anti-␣␤ heterodimer T cell IgM monoclonal antibody), and rabbit complement, We report a patient who developed breast masses 17 months after a T cell-depleted partially mismatched followed by post-BMT immunosuppression with cyclosporine, prednisone, and antithymocyte globulin. Her transplant related donor (PMRD) bone marrow transplant (BMT) for chronic myeloid leukemia. The patient had severe course was uneventful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…EBV captured interest as a possible breast cancer agent when Labrecque et al [24] reported its presence in breast tissue. Some previous studies have demonstrated a high incidence of male breast cancer in countries with a high incidence of EBV-associated lymphomas [25], identification of EBV in primary breast lymphomas [26], and morphological similarities between nasopharyngeal carcinoma and spinal cord carcinoma [27], supporting the idea of pursuing research into a potential association of EBV and breast cancer.…”
Section: Investigations Of Viral Etiology For Breast Cancermentioning
confidence: 88%
“…EBV captured interest as a possible breast cancer agent when Labrecque et al [24] reported its presence in breast tissue. Some previous studies have demonstrated a high incidence of male breast cancer in countries with a high incidence of EBV-associated lymphomas [25], identification of EBV in primary breast lymphomas [26], and morphological similarities between nasopharyngeal carcinoma and spinal cord carcinoma [27], supporting the idea of pursuing research into a potential association of EBV and breast cancer.…”
Section: Investigations Of Viral Etiology For Breast Cancermentioning
confidence: 88%
“…15,16 When clinical suspicions of LPD were entertained, every effort was made to obtain a tissue biopsy for pathological confirmation of the diagnosis of EBV-LPD. Peripheral blood as well as biopsy tissue samples (whenever possible) were sent for flow cytometric analysis for the presence of abnormal cellular clonality.…”
Section: Diagnosis Of Ebv-lpdmentioning
confidence: 99%
“…It is also well recognised that African Burkitt's lymphoma can target the breast [91][92][93]. It is likely that the morphological similarities between NPC and some lymphocyte-rich types of breast carcinoma, including the rare medullary type, stimulated several workers to hypothesise that EBV could be associated with breast carcinomas in Western societies.…”
Section: Epstein-barr Virusmentioning
confidence: 99%